Gambaran Pemberian Obat Masal Pencegahan Kaki Gajah Di Wilayah Kerja Puskesmas Welamosa Kecamatan Wewaria Kabupaten Ende Tahun 2011-2015 - WILHELMUS OLIN; Mariana Hartini Dhema Deto (JURNAL INFO KESEHATAN, 2017)
Elephant Foot Disease (Lymphatic Filariasis), hereinafter referred to as filariasis, is a chronic infectious disease caused by filarial worms that attack the lymph nodes. Data from the Ende District Health Office shows that up to 2015 there were 233 cases of filariasis with the highest number found in the welamosa Public Health Center in the authority district of 67 people. The purpose of this study was to determine the description of mass drug prevention of elephantiasis in the working area of Welamosa Health Center in Wewaria District, Ende Regency in 2011-2015. The type of research used is descriptive with a cross-sectional design using a stratified random sampling technique with a sample of 380 samples. The results showed that people who drank mass medicine to prevent elephantiasis in 2011 amounted to 51%, in 2012 amounted to 52%, in 2013 amounted to 56%, in 2014 and 2015 respectively 62%. People who do not take medication are caused by not getting medication and not taking medication. Residents who get the medicine but do not drink it are more due to no desire to drink that because of the side effects of drugs/allergies while the people who do not get the medicine are more due to the unwillingness/willingness to take the drug.